Spreadsheet Tools for Engineers using Excel - Gottfried Byron S (New York : McGraw-Hill, 2007)
About the Author
As part of McGraw-Hill's BEST series for freshman engineering curricula, this text is particularly geared toward introductory students. The author provides plenty of background information on technical terms, and numerous examples illustrating both traditional and spreadsheet solutions for a variety of engineering problems. The first three chapters introduce the basics of problem solving and Excel fundamentals. Beyond that, the chapters are largely independent of one another. Topics covered include graphing data, converting units, analyzing data, interpolation and curve fitting, solving equations, evaluating integrals, writing macros, and comparing economic alternatives.
Byron S. Gottfried is a Professor of Industrial Engineering and Academic Director of the Freshman Engineering Program at the University of Pittsburgh. He has written eleven college textbooks, including Schaum's Outline of Programming with Basic.
Contents
Through previous editions, this practical text has found a permanent spot in many introductory engineering courses by successfully combining an introduction to Excel fundamentals with a clear presentation on how Excel can be used to solve common engineering problems. Updated to ensure compatability with all recent versions of Excel, this third edition of Spreadsheet Tools for Engineers provides beginning engineering students with a strong foundation in problem solving using Excel as the modern day equivalent of the slide rule.
Keywords: Electronic spreadsheets; Engineering - Data procession; Microsoft Excel (Computer file)